Emotion work and its relation to job burnout and job satisfaction among call center agents in Iloilo City - Banas, Mechaela E.
The current study aimed to described the level of emotion work among call center agents in Iloilo City including the differences in their levels of emotion work between sex groups and types of call center work. It also attempted to show the relationship of emotion work to job burnout and job satisfaction. The findings revealed that call center agents occasionally have intense experience of emotion work, whereas thay sometimes experience a variety of emotion work. Moreover, they used deep acting regulation of emotion more compared to surface acting. Emotion work is correlated with job satisfaction while no relationship was found between emotion work and job burnout. Significant differences in the levels of emotion work existed both for groups based on sex and type of work.